Performance modelling of windmilling gas turbines - Jones, Geoffrey B. (Cranfield University, 2002)
This thesis presents work carried out with the aim of improving the modelling of windmilling in gas turbine performance. The work also examines the phenomenon of relight. Methods of representing the performance of the turbomachinery components are investigated and recommendations are made for the use of a number of non- dimensional variables on which to map turbomachinery performance. A performance model was built using the turbomachinery characteristics proposed in order to test the robustness of the representations. The model was written in Fortran 90 and coupled directly to a spreadsheet package to allow easy analysis of the results. The effect of choice of representation, in terms of both the robustness and the results obtained, is presented. Techniques for the extrapolation of above-idle turbomachinery characteristics to the sub-idle region for starting and windmilling modelling are examined. A number of techniques are analysed and two new methods are proposed. These are the use of computational fluid dynamics to generate a zero speed torque and pressure loss relationship and the use of a semi-empiricalstage-by-stageextrapolation method. Some aspects of relight combustion, particularly in respect of ignition, are studied. Also investigated were the accessory systems acting on the gearbox of the engine. An assessment of the design process and the consequent benefits to the company of improved modelling were presented, in terms of the reduction in design risks and in project development costs. It was shown that research of this nature can have a substantial impact on an engine's development programme Throughout the doctoral programme, Masters and exchange students were used to broaden the scope and depth of the research. This thesis examines how best to ensure that the results of such collaboration are positive and presents the approach which this researcher used.